Revealing oxidative stress-related genes in osteoporosis and advanced structural biological study for novel natural material discovery regarding MAPKAPK2 - Zhao, Yingjing; Li, Weihang; Zhang, Kuo; Xu, Meng; Zou, Yujia; Qiu, Xiaotong; Lu, Tianxing; Gao, Bo (Frontiers in Endocrinology, 2022)
Objectives: This study aimed to find novel oxidative stress (OS)-related biomarkers of osteoporosis (OP), together with targeting the macromolecule MAPKAPK2 protein to further discover potential novel materials based on advanced structural biology approach. Methods: Gene expression profiles of GSE35958 was obtained from GEO database, which were included for WGCNA (weighted gene co-expression network analysis) and differential analysis to identify the most correlated module, to identify OS-related hub genes in the progression of OP. Functional annotations were also analyzed on the interested module to get comprehensive understanding of these genes. Then a series of advanced structural biology methods, including high-throughput screening, pharmacological characteristics prediction, precise molecular docking, and molecular dynamics simulation etc., were implemented to discover novel natural inhibitor materials against MAPKAPK2 protein. Results: Brown module containing 720 genes were identified as the interested module, and a group set of genes were determined as the hub OS-related genes, including PPP1R15A, CYB5R3, BCL2L1, ABCD1, MAPKAPK2, HSP90AB1, CSF1, RELA, P4HB, AKT1, HSP90B1 and CTNNB1. Functional analysis demonstrated that those genes were primarily enriched in response to chemical stress and several OS-related functions. Then novel materials discovery demonstrated that 2 compounds, ZINC000014951634 and ZINC000040976869 were found binding to MAPKAPK2 with favorable interaction energy together with high binding affinity, relatively low hepatoxicity, carcinogenicity, and high aqueous solubility, intestinal absorption levels etc., indicating the 2 compounds were ideal potential inhibitor materials targeting MAPKAPK2. Conclusion: This study found a group set of OS-related biomarkers of OP, providing further insights for OS functions in the development of OP. This study then focused on one of the macromolecules MAPKAPK2 to further discover potential novel materials, which was of great guide significance in screening MAPKAPK2 potential materials.